The complementary and alternative roles of elemene injection in cancer: An umbrella review - Jixin Chen; Shuqi Chen; Huiyan Luo; Xinliang Wan; Wanyin Wu; Sumei Wang (Elsevier, 2023)
Background: In the past, many meta-analyses (MAs) suggested that elemene injection (EI) played a complementary and alternative role in cancer treatment. However, some results were contradictory and a lot of evidences weren't classified. Thus, their clinical guidance effect was very limited. Methods: Two reviewers independently retrieved 8 databases from their origin to May 19, 2023 and appropriate MAs were taken into consideration. A pooled analysis was conducted to merge results extracted from trials of included MAs. The methodological quality of MAs and the evidence certainty of pooled results were assessed. Results: 31 MAs were taken into analysis with poor methodological quality. The main weaknesses were in the areas of heterogeneity analysis, bias risk, and literature selection. According to the present evidence, on the one hand, compared with conventional treatment (CT) alone, EI combined with CT may significantly enhance short-term or long-term efficacy and reduce adverse reactions caused by CT in multiple cancers. On the other hand, using EI alone also can improve ORR in the malignant (pleural) effusion and lessen the recurrence rate in bladder cancer obviously with fewer adverse reactions compared with CT alone. However, this evidence was rated as moderate to very low certainty mainly due to the risk of bias in clinical trials. Conclusion: EI may be a viable medication for the treatment of cancer although more convincing trials are still required to demonstrate its alternative and complementary benefits. Besides, it seems to have a broad potential for further development in immunotherapy, drug delivery technique, and predictive factor.